Necessary Suffering, Bravery of Prey: Commentary on "Dominant Perversions; Perverse Dominance: Eroticized Schemata and Dissociative Phenomena in the Case of Daniel". Issue 1 (2nd January 2022) - Celenza, Andrea
Abstract : The essential experience of suffering with our patients is discussed in relation to Daniel, a man with prominent psychopathy and dissociative disorder. The ways in which the author, Shelley Heusser, was receptive to Daniel despite repeated power plays and doer-done to relational dynamics, is highlighted, with appreciation for Heusser's steadfastness, courage and devotion. Mutual vulnerability and fallibility are discussed as crucial to the development of internal strength for both therapist and patient alike, even as these are attempted to be sadistically vanquished by reciprocal, dyadically triggered "internal predators." Descriptive accounts of perverse scenarios are presented to establish boundaries around which empathy can take root and grow. These do not substitute for mutually living through necessary enactments that may involve life or death struggles.